Cycling as a Healthy Lifestyle Self-Presentation Strategy on Instagram during the Covid-19 Pandemic in Indonesia - Rizki Saga Putra; Nina Mutmainnah (Ikatan Sarjana Komunikasi Indonesia, 2022)
A current study shows the strategy used to build a healthy individual self-presentation by performing cycling on Instagram platform during the Covid-19 pandemic. A positive self-image shown on Instagram account is commonly perceived as a communication pattern in digital social interaction. Given the pandemic situation, cycling as a healthy lifestyle has fast become the most common strategy used by Instagram users to achieve positive self-presentation, by integrating cycling activities data aggregated from Online Social Fitness Networks (OSFNs) platform. This study uses a qualitative method with constructivism paradigm and case study approach. Data collection is conducted through observations and interviews with four informants. Observation is acquired by collecting a series of Instagram feeds and stories of the informants for the past six months of the pandemic. Interviews are conducted to explore both the informantsâ€™ strategies and motivations to present the data in their respective Instagram accounts. The result contends that the â€œfull packageâ€ strategy is the preferable choice for informantsâ€™ self-presentation on Instagram by selecting various locations of background photos and the symbols which confirm their social status, by inserting popular hashtags, by providing links to associate with Instagram glamorous urban cyclistsâ€™ lifestyle content, and by showing off cycling data from OSFNs platform.